Data supporting 'Fibre-Coupled, Multiplexed Methane Detection Using Range Resolved Interferometry' - Bremner, James; Kissinger, Thomas; Hodgkinson, Jane; Tatam, Ralph P. (Cranfield University, 2023)
Dataset for paper: Fig 2 & Fig3: Time of measurement, The OPD being interrogated, The amplitude of the signal produced by the RRI system, The applied window used, The raw interferrometric signal from the photdiode Note: The Time measurement only applies to the measurement of the interferometric signal. The RRI signal amplitude is instantaneous Fig 4: The extracted light intensity passing through each tube as a function of time over the period of one ramp. (arbitary units) Fig 5 Absorption Heights: The height of the normalised absorption curves in each test Fig 5 Recorded Gas Flows: The gas flow measurements in each test that were used to calculate the gas concentrations in each test Fig 6: Allan Deviation: The value for the Allan Deviation at each integration period Fig 7: Cross Talk Raw Data: The height of the normalised absorption curve measured for Tube 1 in each test. Fig 7: Cross Talk Protocol: The gas flow supplied to each tube during each test.
Keywords: Methane'; 'spectroscopy results'; 'Applied Physics'; 'Photonics; Optoelectronics and Optical Communications'